Novel Black Seed Polysaccharide Extract-g-Poly (Acrylate) pH-Responsive Hydrogel Nanocomposites for Safe Oral Insulin Delivery: Development, In Vitro, In Vivo and Toxicological Evaluation - Farya Shabir; Asif Mahmood; Nadiah Zafar; Muhammad Zaman; Rai Muhammad Sarfraz; Hira Ijaz (MDPI AG, 2022)
Oral delivery of insulin has always been a challenging task due to harsh gut environment involving variable pH and peptidase actions. Currently, no Food and Drug Administration (FDA) approved oral insulin formulation is commercially available, only intravenous (IV) or subcutaneous (SC) routes. Therefore, it is really cumbersome for diabetic patients to go through invasive approaches for insulin delivery on daily basis. In the present study, a novel pH-responsive hydrogel nanocomposite (NC) system was developed and optimized for safe oral delivery of insulin. Black seed polysaccharide extract-based hydrogel (BA hydrogel) was formulated by free radical polymerization and loaded with insulin. Blank BA hydrogel was also incorporated with insulin-loaded montmorillonite nanoclay (Ins-Mmt) to form an Ins-Mmt-BA hydrogel NC and compared with the insulin-loaded hydrogel. Swelling, sol-gel analysis and in vitro release studies proved that Ins-Mmt-BA6 hydrogel NC has the best formulation, with 96.17% maximum insulin released in 24 h. Kinetic modeling applied on insulin release data showed the Korsemeyer-Peppas model (R2 = 0.9637) as the best fit model with a super case II transport mechanism for insulin transport (n > 0.89). Energy Dispersive X-ray (EDX) Spectroscopy, Fourier Transformed Infrared (FTIR) spectroscopy and Powdered X-ray diffraction (PXRD) analysis results also confirmed successful development of a hydrogel NC with no significant denaturation of insulin. Toxicity results confirmed the safety profile and biocompatibility of the developed NC. In vivo studies showed a maximum decrease in blood glucose levels of 52.61% and percentage relative bioavailability (% RBA) of 26.3% for an Ins-Mmt-BA hydrogel NC as compared to BA hydrogels and insulin administered through the SC route.